Is there a role for hand-to-genital sexual transmission of human papillomaviruses? Results from the HITCH cohort study - Malagón, Talía (Lancet Infect Dis, 2019)
BACKGROUND: Hand-to-genital contact is hypothesized to be a transmission mode of HPV of genus Alphapapillomavirus. We compared the relative importance of hand-to-genital and genital-to-genital HPV transmission between sexual partners. METHODS: We recruited and followed-up female university students 18-24 years old and their male sexual partners in Montréal, Canada (2005-2011). Partners provided hand and genital samples, which we tested for DNA of 36 HPV types using PCR. We assessed predictors of incident type-specific HPV detections using Cox proportional hazards models. FINDINGS: 264 women and 291 men had valid hand samples. The hazard ratio (HR) of incident female genital HPV detection was 5·0 (95% confidence interval [CI] 1·5-16·4) when her partner was same type hand-positive vs -negative, but adjustment for his genital HPV status reduced the HR to 0·5 (95%CI 0·1-1·8). Similarly, the HR of incident male genital HPV detection was 17·9 (95%CI 7·9-38·5) when his partner was same type hand-positive vs negative, but adjustment for her genital HPV status reduced the HR to 2·3 (95%CI 0·9-6·2). Conversely, the HR of type-specific incident genital HPV detections associated with partner genital HPV positivity was 19·3 (95%CI 11·8-31·8) for females and 28·4 (95%CI 15·4-52·1) for males after adjustment for their hand HPV status. INTERPRETATION: Clinicians can reassure their patients that HPV transmission is unlikely to occur through hand-to-genital contact. The majority of genital HPV infections are likely caused by genital-to-genital sexual transmission. FUNDING: Canadian Institutes for Health Research, National Institutes of Health, Fonds de la Recherche en Santé du Québec, Merck & Co. Ltd.